Synthesis, mechanical and corrosion behaviour of iron–silicon carbide metal matrix nanocomposites - Khosla P.; Singh H.K.; Katoch V.; Dubey A.; Singh N.; Kumar D.; Gupta P. (My University, 2025)
The present paper reports the effect of sintering temperature on the properties of Fe–SiC metal matrix nanocomposites (5 wt% SiC; 95 wt% Fe) prepared by powder metallurgy technique. Samples were synthesized by ball milling followed by compaction and then sintering in the temperature interval of 900 – 1100℃ for 3 h, respectively. X-ray diffraction, microstructure, density, hardness, wear and corrosion of prepared samples have been investigated. X-ray diffraction studies show the presence of iron (Fe) and silicon carbide (SiC) along with the presence of iron silicate (Fe3Si) phase. Iron silicate is formed as a result of reactive sintering between iron and silicon carbide particles. Scanning electron microscopy of the samples shows the dispersion of SiC in the whole Fe matrix. Density, hardness, wear and corrosion characteristics of the samples were investigated which varies for different sintering temperature interval. It is expected that the results of this paper will be helpful in developing metal matrix nanocomposites for various industrial applications. © 2017, © The Author(s) 2017.